The causal role of phoneme awareness and letter-sound knowledge in learning to read: combining intervention studies with mediation analyses. - Hulme, C; Bowyer-Crane, C; Carroll, J; Duff, F; Snowling, M (2012)
There is good evidence that phoneme awareness and letter-sound knowledge are reliable longitudinal predictors of learning to read, though whether they have a causal effect remains uncertain. In this article, we present the results of a mediation analysis using data from a previous large-scale intervention study. We found that a phonology and reading intervention that taught letter-sound knowledge and phoneme awareness produced significant improvements in these two skills and in later word-level reading and spelling skills. Improvements in letter-sound knowledge and phoneme awareness at the end of the intervention fully mediated the improvements seen in children's word-level literacy skills 5 months after the intervention finished. Our findings support the conclusion that letter-sound knowledge and phoneme awareness are two causal influences on the development of children's early literacy skills.